Transformational leadership and development of intellectual capital management stages towards hospital performance / Hazlina Hassan … [et al.] - Hassan, Hazlina; Mohd Saleh, Norman; Kamaluddin, Amrizah; Hamzah, Noradiva (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
Malaysia healthcare industry is facing challenges from a rapidly changing operating environment, including spiralling operating costs and expectations on the quality of healthcare. The government is determined to position Malaysia as a hub for healthcare services for the region. High performance in hospitals is achieved through professionals’ competencies in application of knowledge, technologies and other intangible resources which is also known as Intellectual Capital (IC). A shortage of skilled workforce is always a real challenge for hospital; a high demand for a skilled worker especially in healthcare sector will give a significant impact toward the IC of an organisation. Thus it affects the performance of a hospital in providing a top notch service if the hospital keeps on losing its skilled workers. By acknowledging this reality; the management of the hospital needs to formulate a sound strategic planning of IC which should be executed by a clear, determine, focus and capable leader. Thus, the role and sustainability of both public and private hospitals within this environment, to a large extent depend on the characteristics of the leaders who can manage their IC wisely. It seems that the awareness of the importance of IC has been created in this industry, but how far have these IC elements been measured and managed systematically? Very little empirical research has been done to evaluate the linkages between leadership styles and the management of Intellectual Capital in healthcare industry especially hospital. Therefore, the objective of this paper is to discuss on how transformational leadership styles affect the development of Intellectual Capital Management (ICM) stages that would in turn affect the performance of private and public hospitals. The aim of this paper is to propose a theoretical model that explains the above issues. In addition, more rigorous research methods are needed in order to test and validate the Upper Echelon Theory which is newly introduced for this IC field.